Factors Related to The Utilization of Integrated Healthcare Center by Mothers of Toddlers in Camplong I,Kupang - Ardila M Langata; Intje Picauly; Daniela L. A. Boeky (Lontar : Journal of Community Health, 2022)
The integrated healthcare center is one of the health facilities established as an effort by the government to suppress MMR, IMR, AKABA, and improve nutrition. Through integrated healthcare centers, intensive monitoring of the growth and development of toddlers can be carried out as well as early detection of cases of malnutrition in children under five through routine weighing every month. This study aims to determine the factors related to the use of integrated healthcare centers by mothers of toddlers in Camplong I Village, Camplong Health Center Work Area, Fatuleu District, Kupang Regency. This cross-sectional study consisted of 121 respondents who were selected using a total sampling technique. Data were analyzed using chi-square and multiple logistic regression. Based on the results of the study, the variables related to the use of integrated healthcare centers by mothers of toddlers were work variables (p = 0.001), integrated healthcare center cadre support (p = 0.007), family support (p = 0.000) and distance (p = 0.040). The logistic regression analysis results showed that the family support variable was the dominant variable associated with the use of integrated healthcare centers by mothers of children under five. Meanwhile, knowledge and perception variables have no relationship with the help of integrated healthcare centers by mothers of children under five.